Analysis of the kinetics of bainite formation below the MS temperature. (15th July 2017) - Samanta, Santigopal; Biswas, Pinaki; Singh, Shiv Brat
Abstract: The kinetics of the isothermal product formed below the M S temperature in 0.32C-1.78Mn-0.64Si-1.75Al-1.20Co (wt%) steel has been analyzed. It has been shown that the diffusion controlled growth rate of pearlite using Zener-Hillert model is too slow to explain the observed kinetics at such a low temperature. The isothermal product cannot be identified as the eutectoid phases. However, an existing model of carbide precipitation from supersaturated ferrite correctly predicts the precipitation observed in bainitic ferrite plate. The results indicate that bainitic ferrite is supersaturated with carbon when it first forms and therefore indicated a displacive mechanism of transformation. Graphical Abstract: